God “To Come”: Between an Onto-theological Presence and Messianic Absence (In memoriam Jacques Derrida) - Oniščik, Marija (Religija ir kultūra, 2014)
The essay, dedicated to the 10th anniversary of Jacques Derrida’s passing, attempts to consider some of the aspects of his views on religion. The notions of différance and “trace” help to reflect on the categories of time and space; the traditional opposition between “Greek” and “Jewish” ways of thinking is treated as a tension between an onto-theological presence and a messianic promise; the very project of Deconstruction is presented as “messianic”.